The secret wound : love-melancholy and early modern romance - Wells, Marion A. (Figurae (Stanford, Calif.), 2007)
Offers a reading of early modern romance in the light of historically contemporary accounts of mind, and specifically the medical tradition of love-melancholy. This book establishes a detailed historical basis for investigating the psychological structure of romance. It investigates the central critical problem of early modern subjectivity.